Respons Pemberian Kombinasi Dosis Pupuk Organik Hayati dan Pupuk NPK Urea terhadap Penyakit Jagung Manis (Zea mays L. Saccharata sturt) MS-Unsika di Kabupaten Sumedang - Hasanah, Siti Nissaul; Syafi’i, Muhammad; Afifah, Lutfi; Bahruzin, Bahruzin (JURNAL AGROPLASMA, 2025)
Sweet corn is one of the products of food crops products that until now the demand for these products is getting rapid. One of the limiting factors for the growth of sweet corn plants is nutrients. The state of nutrients in the soil greatly determines the yield of sweet corn because it can protect against various plant diseases. The effort to overcome this is by fertilizing, both using organic and inorganic fertilizers. The purpose of this study is to determine the response of a combination of doses of biological organic fertilizer and NPK Urea fertilizer to the main disease of sweet corn plants (Zea mays L. saccharata Sturt ) MS-Unsika in Sumedang Regency. This research was carried out on land owned by Biomethagreen (Educational House) on Banjar Sari Street, Awisurat Hamlet, Tanjungsari Village, Tanjungsari District, Sumedang Regency, West Java Province. The research method used in this study is a Single Group Random Design (RAK) consisting of 5 treatments that are repeated 5 times, so there are 25 experimental units. The results of the study showed that the treatment (P3) of organic fertilizer dose of 7 cube/ha plus 150+100 kg/ha of NPK and Urea inorganic fertilizer gave the best results against disease resistance in sweet corn, namely leaf blight with a stable average incidence of 1.26%, gray leaf spot disease with an average incidence of 0.8%, leaf rust disease with an average incidence of 0.07%. The conclusion is that there is a good response to the use of organic fertilizers and inorganic fertilizers simultaneously and in balance to the control of sweet corn plant diseases. Keywords: sweet corn, organic fertilizer, inorganic fertilizer, plant disease